RANCANG BANGUN APLIKASI PENGENTASAN MASALAH MAHASISWA MENGGUNAKAN METODE CASE-BASED REASONING PADA BAGIAN BIMBINGAN KONSELING UNIVERSITAS DINAMIKA BERBASIS WEB - Hangga Yuda Rozaqi; Vivine Nurcahyawati; Bambang Hariadi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
In the implementation of the guidance and counseling program, the counselor has not been supported by a computerized system and is connected to the PPTI Undika section database in fulfilling the data needs of students and lecturers for counseling activities. The next problem is counselor only provides one place to store counseling documentation by month. This is very ineffective in the counseling process, especially for the process of alleviating student problems. The counselor should not have moved and looked for old case counseling documentation to diagnose new case problems that are being experienced by students during the counseling process. Alleviation is part of counseling, counseling is the process of handling individual problems assisted by a professional, namely the counselor voluntarily to change the patient's behavior. The problem alleviation process is a problem-solving process. Applying the Case-Based Reasoning method in the process of alleviating student problems for the BK Section is a suitable solution to the problems identified. The author here provides a solution in the form of designing student problem alleviation applications in the Counseling Guidance Section with a web-based case-based reasoning method. The application of Case-Based Reasoning in the system consists of 2 paths. The first path is to match new cases with the diagnosis of problems in the knowledge base (Retrieve). If a similarity is found between the two, the system will adapt the diagnosis to be included in the Counseling Medical Record (Reuse). The second path, if there is no match of diagnosis between the new case and the knowledge base, the system will direct the counselor to a revised form to modify the diagnosis of new cases to be stored and add data to the knowledge base (Revise). The last process in this second route is to save the diagnosis of the new case into a database (Retain). This solution aims to assist the counselor in diagnosing the problem and proceeding to the alleviation process so as to produce output in the form of Counseling Medical Records, Student Counseling Summary and Guidance and Counseling Program Implementation Reports. From the results of this design it is suggested for future research by developing user interface designs and implementing good solutions for the webbased display of the Student Problem Alleviation Application. Because the weakness in this study is that it is not yet able to implement a comfortable application interface for the user.